Pengaruh Kompetensi, Audit Tenure Dan Independensi Auditor Terhadap Kualitas Audit Di Kantor Akuntan Publik Kota Palembang - Chairani Adelina; Linggariama Linggariama; Rizki Sindy Manopo (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This research aims to determine the influence of competency, audit tenure, and independence on audit quality at Public Accounting Firms (KAP) in Palembang City. This research uses quantitative methods. The population for this research was all auditors in Palembang City and the sample was taken using a purposive sampling method of 32 auditors. The variables in this research are competence, audit tenure, independence and audit quality. Testing was carried out using classical and multiple linear assumption tests. The results of this research can be concluded that competence and independence have a significant positive effect on audit quality, while audit tenure has a negative effect on audit quality. Keywords: Competency, Audit Tenure, Independence, Audit Quality